Probiotics Affect One‐Carbon Metabolites and Catecholamines in a Genetic Rat Model of Depression. Issue 7 (13th March 2018) - Tillmann, Sandra; Awwad, Hussain M.; Eskelund, Amanda R.; Treccani, Giulia; Geisel, Juergen; Wegener, Gregers; Obeid, Rima
Abstract : Scope: Probiotics may influence one‐carbon (C1) metabolism, neurotransmitters, liver function markers, or behavior. Methods and results: Male adult Flinders Sensitive Line rats (model of depression, FSL; n = 22) received Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 (10 9 or 10 10 colony‐forming units per day) or vehicle for 10 weeks. The controls, Flinders Resistant Line rats (FRL, n = 8), only received vehicle. C1‐related metabolites were measured in plasma, urine, and different tissues. Monoamine concentrations were measured in plasma, hippocampus, and prefrontal cortex. Vehicle‐treated FSL rats had higher plasma concentrations of betaine, choline, and dimethylglycine, but lower plasma homocysteine and liver S‐adenosylmethionine (SAM) than FRLs. FSL rats receiving high‐dose probiotics had lower plasma betaine and higher liver SAM compared to vehicle‐treated FSL rats. FSLs had higher concentrations of norepinephrine, dopamine, and serotonin than FRLs across various brain regions. Probiotics decreased plasma dopamine in FSLs in a dose‐dependent manner. There were no detectable changes in liver function markers or behavior. Conclusions: Probiotics reduced the flow of methyl groups via betaine, increased liver SAM, and decreased plasma dopamine and norepinephrine. Since these changes in methylation and catecholamine pathways are known to be involved in several diseases, future investigation of the effect of probiotics is warranted. Abstract : Administration of Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 increases liver S‐adenosylmethionine and lowers plasma dopamine and norepinephrine in an animal model of depression. The methylation and catecholamine pathways are interrelated and involved in several diseases, suggesting that probiotics may influence health by altering C1 metabolism or catecholamines.